Vocal Fold Paralysis after Esophagectomy for Carcinoma. (3rd May 2016) - Loochtan, Michael J.; Balcarcel, Daniel; Carroll, Elizabeth; Foecking, Eileen M.; Thorpe, Eric J.; Charous, Steven J.
Abstract : Objectives: (1) To recognize factors that contribute to vocal fold paralysis (VFP) after esophagectomy. (2) To describe the morbidity associated with VFP after esophagectomy. Study Design: Retrospective cohort study. Setting: Tertiary care academic medical center. Subjects and Methods: The medical records of 91 patients undergoing esophagectomy for malignancy were reviewed (2008‐2014). Twenty‐two patients with postoperative VFP were compared with 69 patients without VFP with regard to preoperative variables, surgical approach (transcervical vs other), and postoperative outcomes. A subset analysis of cervical approaches was performed, including those where an otolaryngologist assisted. Results: There were no significant differences in preoperative variables between patients with and without VFP. Cervical approaches were associated with increased VFP ( P <. 0001). Recurrent laryngeal nerve (RLN) identification was associated with increased VFP ( P =. 0001). RLN dissection by head and neck surgeons was associated with decreased VFP ( P =. 0223). Patients with VFP had longer lengths of stay ( P =. 0078), higher rates of tracheotomy ( P =. 0439), and required more outpatient swallow evaluations ( P =. 0017). Mean time to diagnosis of VFP was 45.6 days (median, 7.5 days). Conclusions: Cervical approaches are associated with increased VFP in patients undergoing esophagectomy for malignancy. When cervical approaches and mobilization are required, the inclusion of an experienced cervical surgeon to identify the RLN may improve the rate of postoperative VFP. Patients with VFP after esophagectomy experience significantly more morbidity. Due to the potential delay in diagnosis and treatment of postoperative VFP, routine assessment of inpatient vocal fold function may be beneficial.